Partisipasi Masyarakat Dalam Pengelolaan Sampah Rumah Tangga Di Kampung Iklim Ngadirejo - Tumimomor, Albertin Yesica Stevani; Lasso, Aldi Herindra (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
Ngadirejo Climate Village has initiated household waste management since 2015. The waste bank is an alternative activity in overcoming the problem of household waste. Therefore, this research aims to explain the participation of the Ngadirejo Climate Village community in waste management. This research was conducted in RW 07, Ngadirejo Village, Kartasura, Sukoharjo, Central Java Province. This research uses a quantitative method with a survey with a research sample of 213 heads of families. Data were analyzed descriptively and presented in the form of tables and graphs. The research results show that community participation is relatively high. People no longer burn (71%) and litter (78%). The community has collected and sorted waste according to type. Inorganic waste is landfilled in waste banks. For organic waste, the compost is only 36%. Most people already use reduce, reuse, and recycle. As many as 96% of respondents knew the benefits and impacts of waste banks on society.